Kajian Nilai Estetis dan Simbolis Ukiran Masjid Mantingan Jepara - abdulloh eizzi irsyada (Jurnal Desain Komunikasi Visual Asia, 2019)
The Mantingan Mosque is an old mosque founded by a Duke of Jepara, Sultan Hadlirin and his wife Ratu Kalinyamat in 1481 Saka or 1559 AD. Besides having beauty in the architecture of the building, it also has ancient ornaments patterned with flowers, plants, animals and others that are beautifully carved around its walls. The diversity of motifs, shapes and patterns of each carving makes researchers interested in knowing what are the aesthetic and symbolic values ​​contained in each carving ornament on the walls of the Mantingan Jepara mosque. Aesthetic values ​​are represented in a carving media which is then designed to be fully carved into beautiful, intricate, "ngremit" (sophisticated) and "ngrawit" ornaments as indicators of progress and the high expertise and skills of Jepara carving artists at that time. While its symbolic value is full of the philosophy of life represented by the form of communication between the leader (Queen) of Jepara at that time to its citizens.